If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (1 + -6t) = 55 Remove parenthesis around (1 + -6t) 1 + -6t = 55 Solving 1 + -6t = 55 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -6t = 55 + -1 Combine like terms: 1 + -1 = 0 0 + -6t = 55 + -1 -6t = 55 + -1 Combine like terms: 55 + -1 = 54 -6t = 54 Divide each side by '-6'. t = -9 Simplifying t = -9
| 8x+16=12x-60 | | 1/3(12c-9)=-7 | | -6-5-(1-6i)= | | 3b+1-b=17 | | 172-72x=17 | | 10sin(2x)-1=x | | 90=2x-2+x+5 | | 1/6x-4 | | 7/2d-2/d=3/4-1/4d | | (9+4d)=15 | | 12(2k+11)=+12(2k+12) | | 22=64+m | | 2n+16=5n-5 | | -19x+5y=-17 | | K*-3-11=-20 | | -8=3(x-2) | | 550=8x | | 2(9x+9)-10x=8x+6-10 | | 7-6X=1.2-2X | | B-9/10b+6=11 | | 5/2-1 | | 5x-2x=51 | | 6h-15+12h+8=11 | | 5x-2+3x^2=0 | | 8(w+6)=7w-2 | | 350+x=3650 | | 2/3r+4=12 | | (-7i)+(2i)-(-2-4i)= | | -3(7x-5)+8=-21x+23 | | f(x)=-4+8 | | 12(2+2z)=-4z-4(-12z-1) | | (32.50x+3.30)+5.90x=220.70 |